Подружні зради як наслідок практики укладання шлюбів в Україні в XVI - XVIІ ст. (на матеріалах ранньомодерної Волині) - Ворончук, І. (Соціум. Альманах соціальної історії, 2006)
The article deals with an almost unresearched to date problem of marital infidelity in early modem Ukraine. The author proves the idea of independent noble woman, popular in Ukrainian historiography, to be wrong. By analyzing the law regulations and social practices the author proves that in the 16th and 17th centuries the nobles followed patriarchal family norms with the husband executing power over all members of family, wife included. The financial reasons for marriage and lack of emotional ties between spouses caused not only husbands acting brutal towards their wives but also seldom were the reason behind infidelity.